Transformation of Pharma Curriculum as Per the Anticipation of Pharma Industries-Need to Empower Fresh Breeds with Globally Accepted Pharma Syllabus, Soft Skills, AI and Hands-on Training - Malviya, Neelesh; Malviya, Sapna; Dhere, Manisha (Indian Journal of Pharmaceutical Education and Research, 2023)
In this domain of specialty and globalization the pharmacy teaching and learning in India is suffering from serious backdrops and flaws. In India, in present-day need of pharmacy is to physique and shape strategies for a renovated innovative future for affordable and effective healthcare system. There is a crucial necessity to begin an academic exercise aimed at renewing of prospectus, focusing recent and evolving learnings in the field of pharmacy. The current youth of pharmacy graduate sought to have technical expertise of sophisticated instrument functioning, trouble shooting, product and process development, IPR, innovative rational based thinking, quality by design, regulatory aspects of global level to match the anticipation of industrial revolution of pharma 4.0. Certainly, they are short age of expertise in new generation instruments, latest development in Pharma Industry, Intellectual Property Rights and Regulatory needs of Industries and profound exposure of Process Analytical Technology (PAT). The numerous factors which should be well-known are Environmental Health and Safety (EHS), Investigation like 6 sigma’s, Ishikawa Fish bone skills and CAPA, Parameters Efficiency including OEE, SMED, 5S, OPE, Lean production, Latest Development of Pharma Industries, Regulatory knowledge about Internal and External Audits, Self-Inspections, technology Transfer, Change Management emphasizing on Control on changes and Risk management: FMECA, Risk Evaluation and Mitigation. Artificial intelligence (AI) has the potential to bring about a paradigm shift in the way drug are researched, developed and marketed. AI is changing the pharmaceutical industry by looking at 5 key areas of AI in pharma: data science, drug discovery, clinical trials, marketing and R&D. The article emphasizes on raising the current standards of knowledge, skills and domain of scholars of Diploma, Bachelors, Masters and Doctorate of Pharmacy course. The necessity of an hour is to work on enhancing the concept of innovation and quality management. Solicitation of technical expertise to the educational system improves the present situation. The admission procedures should be brought underneath the scanner as these are the opening of the students for entrance in the profession. Gaining expertise at bachelor’s level will lead to proficiency and brilliance.
Keywords: Pharmacy Education; Pharma Industries; Latest Development; Pharma 4.0; Artificial Intelligence